Application of design of experiments on the simulation of a process in an automotive industry - Barra Montevechi, Jose Arnaldo; Pinho, Alexandre Ferreira de [UNESP]; Leal, Fabiano [UNESP]; Silva Marins, Fernando Augusto [UNESP]; IEEE (Ieee, 2007)
The objective of this article is to apply the Design of experiments technique along with the Discrete Events Simulation technique in an automotive process. The benefits of the design of experiments in simulation include the possibility to improve the performance in the simulation process, avoiding trial and error to seek solutions. The methodology of the conjoint use of Design of Experiments and Computer Simulation is presented to assess the effects of the variables and its interactions involved in the process. In this paper, the efficacy of the use of process mapping and design of experiments on the phases of conception and analysis are confirmed.